Migration, health, and development - Lahiri, Subrata; Paswan, B.; Das, K. C. (Rawat Publications, 2011)
Migration, health, and development are considered to be the three interrelated issues in the present development scenario. This book, which examines the linkages between these three areas, is based on the analysis of both micro and macro data drawn from censuses, large sample surveys, and field studies primarily conducted in Asian countries, with special emphasis on India. With 20 research papers thematically arranged into five sections - Migration and Urbanization; Population, Development, and Environment; Ageing; Demography of Ethnic Groups; and Population Policies and Programs - the book promises to be of immense value for social scientists, including population scientists, urban and regional planners, policy makers, and administrators. Selected papers on population, internal migration, and reproductive health of the population presented at the International Conference on Emerging Population Issues in the Asia-Pacific Region: Challenges for the 21st Century on 10-13, December, 2006 at International Institute for Population Sciences, Mumbai.